Effectiveness of Health Education Techniques in Enhancing the Knowledge of Zika Virus Diseases among the Staff Nurses Working in Selected Hospitals of Biratnagar, Nepal - Poudel, Surakshya; Subramaniam, Umashankar (Journal of Nobel Medical College, 2025)
Background: Zika Virus Diseases has become a concern in the South-East Asia region. Aedes aegypti, the vector of the diseases, is already present in Nepal. Educating health workers is one of the most cost-effective measures to address emerging health problems. This study aimed analyses the effective technique to increase the knowledge among nurses about diseases.Materials and Methods: Pre and post study design was used. Total 5 hospitals among 19 hospitals of Biratnagar Metropolis were randomly selected in first stage. In second stage,25 nurses from each 5 hospitals were selected randomly making total sample size of 125. Different health education techniques were assigned to groups using a lottery method. The health education techniques included participatory lecture with PowerPoint presentation, video session, pamphlet distribution, and poster presentationResults: At the first post-test, the group subjected to video sessions and pamphlet showed highest mean knowledge scores (15.12, Std. deviation = 1.764 and 1.787, respectively). However, the participatory lecture group displayed the highest percentage increase in knowledge score (50.31%) in comparison to pretest. After the second post-test, the group exposed to poster presentations had the highest mean knowledge score (13.72, Std. deviation = 2.112). Nevertheless, the group undergoing participatory lectures with PowerPoint presentations still demonstrated the highest percentage increase in knowledge score (51.1%).Conclusion: Participatory lecture with power point presentation was the most effective measure to disseminate information about Zika Virus Diseases as the difference in knowledge score was significant.